2009
DOI: 10.1017/s1360674309990141
|View full text |Cite
|
Sign up to set email alerts
|

The grammaticalization and subjectification of adverbial -ingclauses (converb clauses) in English

Abstract: The present article discusses the development of adverbial -ing clauses, so-called ‘converb clauses’, in English. We argue that Middle English does not have a category of truly subordinate adverbial clauses in -ing, but that such clauses have developed on the basis of semi-coordinate -ing clauses denoting an accompanying circumstance or exemplification/specification. In the course of the Middle English period, such clauses began to be reinterpreted as clauses expressing adverbial relations such as time, condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
21
0
5
Order By: Relevance
“…Turning from adjuncts to disjuncts, and comparing the figures in Table 5 to the situation for disjunctively used PCs, it is found that the latter also saw an increase in use, but the main surge in frequency occurred much earlier in the transition from the Middle to Killie & Swan 2006). There is considerably less ground, therefore, to suspect that disjunct-based reanalysis would have been delayed by frequency-dependence in the same way as adjunct-based reanalysis.…”
Section: Sources and Diffusionmentioning
confidence: 96%
“…Turning from adjuncts to disjuncts, and comparing the figures in Table 5 to the situation for disjunctively used PCs, it is found that the latter also saw an increase in use, but the main surge in frequency occurred much earlier in the transition from the Middle to Killie & Swan 2006). There is considerably less ground, therefore, to suspect that disjunct-based reanalysis would have been delayed by frequency-dependence in the same way as adjunct-based reanalysis.…”
Section: Sources and Diffusionmentioning
confidence: 96%
“…Once the verbal gerund had become established, clausally grounded bare nominal gerunds were lost, leaving the verbal gerund to be the only gerundive subschema that can take unambiguously clausal deixis. With their newly acquired clause-like status, verbal gerunds then further expanded and strengthened their position in the English ing-network through so-called "horizontal links" with another construction with a similar form that is not interparadigmatically related (Van de Velde, 2014; Norde, 2014), as they started to interact with present-participial clauses (Fanego, 1996(Fanego, , 1998Kohnen, 1996Kohnen, , 2001Kohnen, , 2004Killie & Swan, 2009;De Smet, 2010;Fonteyn & van de Pol, 2015). Yet, crucially, the verbal gerund did not weaken or loosen its ties to the nominal gerund and its overarching noun phrase schema: as the formal neoanalysis of the gerund operated autonomously, verbal gerunds that fully aligned with a zero-grounded nominal analysis gradually increased in frequency as well.…”
Section: Reflections On Category Change: Is the Verbalization Of The mentioning
confidence: 99%
“…A similar example of subjectification in secondary grammaticalization occurred when English adverbial -ing clauses, which at first merely expressed an additional or accompanying circumstance, came to express concessive, causal and conditional meanings (Killie & Swan 2009 Recently a number of scholars (e.g. Norde 2009, Kranich 2010, Traugott 2010 have suggested that subjectification first and foremost takes place in the early stages of grammaticalization, in the pragmatic strengthening processes which make grammaticalization possible in the first place:…”
Section: Subjectificationmentioning
confidence: 99%